Impact of CdTe thin film thickness in ZnxCd1?xS/CdTe solar cell by RF sputtering - Hossain M.S.; Rahman K.S.; Karim M.R.; Aijaz M.O.; Dar M.A.; Shar M.A.; Misran H.; Amin N. (Elsevier Ltd, 2023)
Atomic force microscopy; Cadmium sulfide; Cadmium sulfide solar cells; Cadmium telluride; Crystallinity; Efficiency; Film thickness; Glass; II-VI semiconductors; Lime; Magnetron sputtering; Optical properties; Scanning electron microscopy; Semiconductor alloys; Silver compounds; Thin film solar cells; Uranium metallography; Vanadium metallography; X ray diffraction; Zinc; Zinc metallography; Zinc sulfide; CdTe; Cell configurations; Optimum deposition; rf-Magnetron sputtering; Rf-sputtering; Structural and optical characterizations; Window layer; Zinc blend structure; Thin films; cadmium; film; fuel cell; scanning electron microscopy; solar power; tellurium; X-ray diffraction; zinc